al-Makhṭūṭāt al-ʿArabiyya fī Salṭanat ʿUmān - Wahībī, Muḥammad Saʿīd Nāṣir al- (مجلة معهد المخطوطات العربية, 1978)
Sixteen published works and 249 MSS (not all of them Ibāḍī works) out of the 2500 MSS then in MNHC are listed.
Keywords: Manuscrits -- Oman

Oman - Abdul Karim, Bakri Musa (World survey of Islamic Manuscripts, 1993)
Keywords: Manuscrits -- Oman

The Omani Manuscript Collection at Muscat. Part II: The Early Ibāḍī Fiqh Work - Wilkinson, John Craven (Arabian Studies, 1978)
Keywords: Manuscrits -- Oman

The Omani Manuscript Collection at Muscat. Part I: A general Description of the MSS - Smith, G. Rex (Arabian Studies, 1978)
Keywords: Manuscrits -- Oman